The Transformation of Tourism Villages Through Social Capital and Leadership in Turi District, Sleman, Yogyakarta - Istriyani, Ratna (Journal of Contemporary Sociological Issues, 2024)
This research investigates social shifts in Turi District, Sleman Regency, The Special Region of Yogyakarta. Turi District was previously known as a salak fruit-producing area, which developed as a salak agro center. However, Turi District has become the area with the most tourist villages in Sleman Regency. The growth of tourist villages there is relatively rapid and reasonably fast. This research aims to look at the transformation process and the capital supporting the tourist villages' development in the Turi District. The method used in this research is qualitative. The data collection techniques are observation and interviews. Meanwhile, the theories used are social capital and human capital. The research has three main findings. Firstly, the tourist village in Turi District is a shared asset managed collectively and driven by the collective awareness of the local community. Solid social relations and local institutions support this collective awareness. Social capital makes it easier to mobilize community participation in the pilot process and management of tourist villages. Second, the existence of solid bonding relationship capital supported by external network capital with outside institutions (bridging social capital). It further facilitates efforts to develop tourist villages. Third, even though social capital significantly influences the start-up and management of tourist villages, the key factor in intensifying the development of tourist villages comes from actors or leaders who can build ideas and mobilize physical capital and social capital. In other words, human capital is fundamental in developing tourist villages in Turi District. Based on these findings, this research provides an overview of village communities regarding the importance of commodifying village potential through independent management, actualizing social capital, and the significance of local leadership. It is to provide economic benefits for village communities and maintain environmental and cultural assets (environment and culture sustainability). Keywords: human capital, leadership, social capital, tourism villages, transformation